Modeling of pvT behavior of semi-crystalline polymer based on the two-domain Tait equation of state for injection molding. (5th December 2019) - Wang, Jian; Hopmann, Christian; Schmitz, Mauritius; Hohlweck, Tobias; Wipperfürth, Jens
Abstract: The absence of the influence of cooling rate in the pressure–specific volume–temperature (pvT) models makes them inadequate in the process simulation of injection molding. This work derived new equations of state (EoS) from the traditional two-domain Tait model that describes the pvT behavior of semi-crystalline polymers in both molten and solid state. Especially, the cooling rate was considered. The second aim of this work is to solve the discontinuity problem of the traditional two-domain Tait model. A continuous two-domain Tait EoS was developed. A good agreement between the calculations and experimental results was achieved. The new pvT models were successfully applied in the prediction of specific volume as a function of temperature, pressure and cooling rate during injection molding. A higher value of the specific volume was predicted when the cooling rate was considered. Combining the continuous two-domain Tait EoS, more accurate results can be obtained especially at the transition phase from melt to solid of the semi-crystalline polymer. Graphical abstract: Unlabelled Image Highlights: A two-domain Tait model considering the cooling rate for semi-crystalline polymers has been developed. A continuous two-domain Tait model for semi-crystalline polymers has been developed. A good prediction of the specific volume has confirmed the benefits of the new pvT models. The trace of the specific volume in injection molding has been realized by the new pvT models.